PRINS Non-Coding RNA Regulates Nucleic Acid-Induced Innate Immune Responses of Human Keratinocytes - Judit Danis; Judit Danis; Anikó Göblös; Anikó Göblös; Zsuzsanna Bata-Csörgő; Zsuzsanna Bata-Csörgő; Lajos Kemény; Lajos Kemény; Márta Széll; Márta Széll (Frontiers in Immunology, 2017)
Cytosolic DNA fragments are recognized as pathogen- and danger-associated molecular patterns that induce a cascade of innate immune responses. Moreover, excessive cytosolic DNA can enhance chronic inflammation, predominantly by activating inflammasomes, and thereby contributing to the pathogenesis of chronic diseases, such as psoriasis. Psoriasis associated non-protein coding RNA induced by stress (PRINS) is a long non-coding RNA, which has been shown to be associated with psoriasis susceptibility and cellular stress responses; however, the precise mechanism of its action has not been determined. Here, we provide evidence that, in addition to inflammasome activation, cytosolic DNA induces intracellular inflammatory reactions while decreasing PRINS gene expression. Furthermore, PRINS overexpression can ameliorate the inflammatory-mediator production of keratinocytes induced by cytosolic DNA. Overexpression of PRINS resulted in decreased interleukin-6 (IL-6) and chemokine (C–C motif) ligand 5 (CCL-5) expression and secretion. In silico analysis predicted direct binding sites between PRINS and the mRNAs, which was confirmed by an in vitro binding assay and on cellular level. Our results indicated that PRINS binds directly to the mRNAs of IL-6 and CCL-5 at specific binding sites and eventually destabilizes these mRNAs, leading to a decrease in their expression and secretion of the corresponding proteins. These results may indicate a restrictive role for PRINS in inflammatory processes.